2014
DOI: 10.1128/jb.01960-14
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Synthesis of 2-Aminoacrylate Contributes to Cysteine Sensitivity in Salmonella enterica

Abstract: RidA, the archetype member of the widely conserved RidA/YER057c/UK114 family of proteins, prevents reactive enamine/imine intermediates from accumulating in Salmonella enterica by catalyzing their hydrolysis to stable keto acid products. In the absence of RidA, endogenous 2-aminoacrylate persists in the cellular environment long enough to damage a growing list of essential metabolic enzymes. Prior studies have focused on the dehydration of serine by the pyridoxal 5=-phosphate (PLP)-dependent serine/threonine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…IlvE activity was measured in crude lysates as previously described (8). Cultures were grown at 37°C with aeration to stationary phase in 2 ml of NB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IlvE activity was measured in crude lysates as previously described (8). Cultures were grown at 37°C with aeration to stationary phase in 2 ml of NB.…”
Section: Methodsmentioning
confidence: 99%
“…Previous analysis of S. enterica showed that PLP-dependent serine/threonine dehydratases (IlvA/TdcB; EC 4.3.1.19), cysteine desulfhydrase (CdsH; EC 4.4.1.1), and diaminopropionate ammonia-lyase (DpaL; EC 4.3.1.15) generated free 2AA from exogenous serine, cysteine, and diaminopropionate, respectively, leading to complete growth inhibition in the absence of RidA (7,8; D. C. Ernst, M. E. Anderson, and D. M. Downs, submitted for publication). In the absence of exogenous 2AA precursors, basal IlvA activity produced sufficient 2AA from endogenous serine to cause a minor growth defect in ridA strains grown in minimal glucose medium (9).…”
mentioning
confidence: 99%
“…CdsH was provided by D. C. Ernst and was purified as previously described (37). A typical reaction mixture for monitoring the release of pyruvate at A 230 included Tris buffer (50 mM, pH 8.6), pyridoxal-5-phosphate (PLP) (25 M), purified CdsH (0.005 to 5 M), and cysteine, cystine, or S-sulfocysteine (1 mM).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-genome sequencing was used to identify the causative suppressor mutations in S. enterica DM13631 and DM13718 (ptsI611). The protocol used for preparation of genomic DNA has been described previously (36).…”
Section: Methodsmentioning
confidence: 99%